Veno-Venous Extracorporeal Membrane Oxygenation in Minipigs as a Robust Tool to Model Acute Kidney Injury: Technical Notes and Characteristics - Szabó-Biczók, Antal; Varga, Gabriella; Varga, Zoltán; Bari, Gábor; Vigyikán, Gyöngyvér; Gajda, Ámos; Vida, Noémi; Hodoniczki, Ádám; Rutai, Attila; Juhász, László; Nászai, Anna; Gyöngyösi, Máté; et al. (Frontiers in Medicine, 2022)
Objective: Veno-venous extracorporeal membrane oxygenation (vv-ECMO) can save lives in severe respiratory distress, but this innovative approach has serious side-effects and is accompanied by higher rates of iatrogenic morbidity. Our aims were, first, to establish a large animal model of vv-ECMO to study the pathomechanism of complications within a clinically relevant time frame and, second, to investigate renal reactions to increase the likelihood of identifying novel targets and to improve clinical outcomes of vv-ECMO-induced acute kidney injury (AKI). Methods: Anaesthetized Vietnamese miniature pigs were used. After cannulation of the right jugular and femoral veins, vv-ECMO was started and maintained for 24 hrs. In Group 1 (n=6) ECMO was followed by a further 6-hr post-ECMO period, while (n=6) cannulation was performed without ECMO in the control group, with observation maintained for 30 hrs. Systemic haemodynamics, blood gas values and hour diuresis were monitored. Renal artery flow (RAF) was measured in the post-ECMO period with an ultrasonic flowmeter. At the end of the experiments, renal tissue samples were taken for histology to measure myeloperoxidase (MPO) and xanthine oxidoreductase (XOR) activity and to examine mitochondrial function with high-resolution respirometry (HRR, Oroboros, Austria). Plasma and urine samples were collected every 6 hrs to determine neutrophil gelatinase-associated lipocalin (NGAL) concentrations. Results: During the post-ECMO period, RAF dropped (96.3±21 vs 223.6±32 ml/min) and, similarly, hour diuresis was significantly lower as compared to the control group (3.25±0.4 ml/h/kg vs 4.83±0.6 ml/h/kg). Renal histology demonstrated significant structural damage characteristic of ischemic injury in the tubular system. In the vv-ECMO group NGAL levels, rose significantly in both urine (4.24±0.25 vs 2.57±0.26 ng/ml) and plasma samples (4.67±0.1 vs 3.22±0.2 ng/ml), while tissue XOR (5.88±0.8 vs 2.57±0.2 pmol/min/mg protein) and MPO (11.93±2.5 vs 4.34±0.6 mU/mg protein) activity was elevated. HRR showed renal mitochondrial dysfunction, including a significant drop in complex-I-dependent oxidative capacity (174.93±12.7 vs. 249±30.07 pmol/s/ml). Conclusions: Significantly decreased renal function with signs of structural damage and impaired mitochondrial function developed in the vv-ECMO group. The vv-ECMO-induced acute renal impairment in this 30-hr research protocol provides a good basis to study the pathomechanism, biomarker combinations or possible therapeutic possibilities for AKI.